Myricetin attenuates hypoxic-ischemic brain damage in neonatal rats via NRF2 signaling pathway - Chen, Tingting; Hu, Yingying; Lu, Liying; Zhao, Qianlei; Tao, Xiaoyue; Ding, Bingqing; Chen, Shangqin; Zhu, Jianghu; Guo, Xiaoling; Lin, Zhenlang (Frontiers in Pharmacology, 2023)
Hypoxic ischemic encephalopathy (HIE) is a crucial cause of neonatal death and neurological sequelae, but currently there is no effective therapy drug for HIE. Both oxidative stress and apoptosis play critical roles in the pathological development of HIE. Myricetin, a naturally extracted flavonol compound, exerts remarkable effects against oxidative stress, apoptosis, and inflammation. However, the role and underlying molecular mechanism of myricetin on HIE remain unclear. In this study, we would establish the neonatal rats hypoxic-ischemic (HI) brain damage model in vivo and CoCl2 induced PC12 cell model in vitro to explore the neuroprotective effects of myricetin on HI injury, and illuminate the potential mechanism. Our results showed that myricetin intervention could significantly reduce brain infarction volume, glia activation, apoptosis, and oxidative stress marker levels through activating NRF2 (Nuclear factor-E2-related factor 2) and increase the expressions of NRF2 downstream proteins NQO-1 and HO-1. In addition, the NRF2 inhibitor ML385 could significantly reverse the effects of myricetin. In conclusion, myricetin might alleviate oxidative stress and apoptosis through NRF2 signaling pathway to exert the protective role for HI injury, which suggested that myricetin might be a promising therapeutic agent for HIE.